The characteristics of intestinal microflora in infants with rotavirus enteritis, changes in microflora before and after treatment and their clinical values - Qiyan Yan; Yuanyuan Chen; E-Bin Gao; Yanbo Lu; Junhua Wu; Haiyan Qiu (Scientific Reports)
Abstract Rotavirus (RV) is a leading pathogen causing diarrhea in children. In this study, a total of 51 fecal samples from children with RV enteritis, 29 post-treatment fecal samples, and 38 fecal samples from age-matched healthy controls were collected. Microbial DNA was isolated from the samples followed by high throughput Illumina sequencing targeting 16 S rRNA gene. Compared to the healthy group, the RV-infected group exhibited reduced microbial diversity. Both groups shared Firmicutes as the dominant phylum. Additionally, the abundance of Proteobacteria increased significantly in the RV-infected group. At the genus level, among the top 50 most abundant genera, 34 showed significant differences, with these differential genera correlating with certain clinical indicators such as dehydration levels and C-reactive protein (CRP). Notably, there were no significant differences in the microbiota before and after treatment in RV-infected children. Only 8.82% (3/34) of the differential genera in the post-treatment group showed a recovery trend towards the healthy state. This study enhances the understanding of how RV infection alters the gut microbiota structure in children and provides a scientific basis for improving clinical diagnosis and treatment strategies.